2021
DOI: 10.2174/1874447802115010182
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study to Estimate the Economic Effects of the Introduction of a Periodical Technical Inspection (PTI) for Motor Vehicles in Punjab (Pakistan)

Abstract: Aims: In 2016, the government of Punjab (Pakistan) established a new system for inspecting road vehicles. The inspection system tests the roadworthiness, noise level, and emissions from the vehicles. These test metrics have further economic benefits that will be analyzed throughout the study. As the main aim of this study, we provide an economic impact analysis of the introduction of a periodical technical inspection (PTI) system that acts as a basis for political decision-making. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Across the US, states that had an MOT system in place were found to have fewer vehicles on the road with faults. Given the contribution that vehicle faults have in the number of road crashes (estimates ranging from 3% (Cuerden, Edwards & Pittman, 2011) up to 19% (Rechnitzer, Haworth & Kowadlo, 2000) for developed countries), it is clear, based on Murphy et al's (2018) findings and the evidence detailed previously (Schulz & Scheler, 2016;2019), that locations without an MOT system that show a greater number of vehicles with faults, also show a greater number of vehicle fault-based incidents. PPR2028 Murphy et al (2018) also found that crashes involving vehicles with faults were twice as likely to result in a fatality compared to crashes involving vehicles with no defects.…”
Section: Key Findingsmentioning
confidence: 93%
See 1 more Smart Citation
“…Across the US, states that had an MOT system in place were found to have fewer vehicles on the road with faults. Given the contribution that vehicle faults have in the number of road crashes (estimates ranging from 3% (Cuerden, Edwards & Pittman, 2011) up to 19% (Rechnitzer, Haworth & Kowadlo, 2000) for developed countries), it is clear, based on Murphy et al's (2018) findings and the evidence detailed previously (Schulz & Scheler, 2016;2019), that locations without an MOT system that show a greater number of vehicles with faults, also show a greater number of vehicle fault-based incidents. PPR2028 Murphy et al (2018) also found that crashes involving vehicles with faults were twice as likely to result in a fatality compared to crashes involving vehicles with no defects.…”
Section: Key Findingsmentioning
confidence: 93%
“…Their model estimated that in the year 2015, over 34,000 accidents, over 13,000 injuries, and 175 fatalities were avoided because of the MOT system that was in place. The same authors used a similar approach when aiming to achieve a similar objective in an earlier study focused on Turkey (Schulz & Scheler, 2016). Here, there was an estimated reduction of over 82,000 traffic accidents in the year 2008 due to the introduction of the MOT system.…”
Section: Key Findingsmentioning
confidence: 99%
“…Differences in vehicle fleets or vehicle wrecks available for the study may also have had an impact on data obtained for a particular jurisdiction [6]. Likewise, the different levels of quality of the periodic technical inspection systems of the countries studied may make it difficult to compare studies [20].…”
Section: Table 1 Percentage Of Vehicles With Technical Defects That D...mentioning
confidence: 99%
“…As already stated in the analysis, about 335 accidents can be avoided by a regulated introduction of a PTI system, 198 of which would be fatal. The economic loss of 198 fatal accidents amounts to 11.6 million USD, which is a considerable amount for a region like Punjab, whose economic power fades in comparison to that of a developed country [20]. A PTI system would also help in preventing the costs associated with serious or minor injuries.…”
Section: Technical Defects Of Vehicles As the Major Cause Of Traffic ...mentioning
confidence: 99%